Social Determinants of Mental Health and Clinical Updates Featured at Meeting. - O'Brien, Erin; Duerr, Heidi Anne (Psychiatric Times, 2022)
The article presents the highlights of the American Psychiatric Association 2022 annual meeting. Topics include the study on the structural brain effects of practice sparring to mixed martial arts (MMA) fighters, the potential of artificial intelligence (AI) in psychiatry, and the ripple effects of trauma during disasters. Presenters include medical student Aaron I. Esagoff and Duke University School of Medicine's P. Murali Doraiswamy.